2019
DOI: 10.2478/orga-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Motivation of Knowledge Workers – the Case of Albania

Abstract: Background and Purpose:Very little is known about motivation of knowledge workers in the Western Balkans. There is a widespread belief that money and career opportunities are the most critical motivational factors, but from a pre-study more intrinsic motivational factors also appeared to be important. To develop a better understanding of work motivation, a study was conducted among knowledge workers in Albania, with a special interest in the themes of extrinsic / extrinsic motivation and organizational commitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…According to Chipunza and Matsumunyane (2018), work motivation can be seen as an “internal state” that allows employees to be encouraged to achieve organizational goals and good performance results. For Nientied and Toska (2019), the development of new behaviours by employees are due to the organizational context and the personal experiences of each employee, which allow them to increase, or not, their work motivation. However, Glaz et al.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…According to Chipunza and Matsumunyane (2018), work motivation can be seen as an “internal state” that allows employees to be encouraged to achieve organizational goals and good performance results. For Nientied and Toska (2019), the development of new behaviours by employees are due to the organizational context and the personal experiences of each employee, which allow them to increase, or not, their work motivation. However, Glaz et al.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…to Bianchi (2018), the relationship between employees' adaptation and training and their organizations is mediated by shared intrinsic and extrinsic values at work. In the same perspective, Nientied and Toska's (2019), study on motivational factors and organizational commitment of knowledge workers in Albania concludes that "organizations need to pay attention to the relationship between motivation improvement and productivity improvement. The current transactional leadership style stimulates employees based on their innate drive to increase productivity (Jaramillo, 2011, p. 33).…”
Section: Accordingmentioning
confidence: 99%
“…The current transactional leadership style stimulates employees based on their innate drive to increase productivity (Jaramillo, 2011, p. 33). Similarly, Terlato's (2018) research on motivation, intrinsic factors, and performance in companies in the metropolitan area of Buenos Aires shed evidence that "the use of extrinsic factors is little mobilizing, and companies seem to use them in the face of ignorance of the essence of the motivational process" (p. 28) (Nientied and Toska, 2019). This author insists that if companies "want to have people who perform, who improve their tasks, serve customers better, communicate better, and innovate, they must learn to develop the internal drivers for virtuous behavior" (p. 28).…”
Section: Accordingmentioning
confidence: 99%
“…Self-leadership and empowering leadership are still rather unfamiliar concepts in management discussions in the Western Balkans (WB) and in Central and Eastern Europe (CEE) for that matter. Researchers such as Steyrer et al (2006), Lang et al (2013), Auer-Rizi and Reber (2012) and Nientied and Toska (2019) have concluded that traditional/conservative leadership styles of the managers that can be labelled as transactional leadership, still succeed. However, more modern leadership styles also exist in organisations.…”
Section: Introductionmentioning
confidence: 99%